Magnetotransport measurements of connected kagome artificial spin ice in armchair and zigzag configurations - Schiffer, Peter; Le, Brian L. (University of Illinois at Urbana-Champaign, 2017)
Enclosed in this dataset are transport data of kagome connected artificial spin ice networks composed of permalloy nanowires. The data herein are reproductions of the data seen in Appendix B of the dissertation titled "Magnetotransport of Connected Artificial Spin Ice". Field sweeps with the magnetic field applied in-plane were performed in 5 degree increments for armchair orientation kagome artificial spin ice and zigzag orientation kagome artificial spin ice.
Keywords: Magnetotransport; artificial spin ice; nanowires